Derivation of geographical marginalization index of Bosnia and Herzegovina using GIS multicriteria decision analysis - Avdić, Aida; Marić, Ivan (Geographica Pannonica, 2023)
Across Europe marginalization has been highlighted as an object of important political concern. In the area of Central Europe and the Balkans, the problem of marginalization has not been sufficiently researched. This particularly applies to the Bosnia and Herzegovina (BiH). Using the GIS multicriteria decision analysis a composite index of geographical marginalization (GMAR) was created. Marginalization is analyzed as a multidimensional concept using the 4 groups with a total of 40 criteria. Spatial patterns were detected from extremely marginalized to extremely non-marginalized regions. The GMAR indicates the existence of regional disparities in BiH. The high degree of marginalization, especially those in the border sector, alerts the implementation of the demarginalization measures.